Startup accelerators - Michał Bańka; Mariusz Salwin; Aneta Ewa Waszkiewicz; Szymon Rychlik; Maria Kukurba (International Journal of Management and Economics, 2022)
Accelerators have been becoming increasingly popular among young entrepreneurs interested in developing products, attracting investors, or establishing relations with industry represented by large companies. The focus of the studies is to conduct literature review due to the small number of scientific articles are available on this topic. The article aims to show the current state of knowledge about startup accelerators and the support they provide. It outlines what added value accelerators offer in their programs for young innovative companies. To achieve the stated aim, the authors combine a systematic literature review with a bibliometric analysis. The results of this research will be helpful in better matching the developed project with existing accelerator programs on the market. It can contribute to a better understanding of the principles governing the programs, program expectations of the accelerator and its partners with respect to the proposed solutions (corporations, business angels, and venture capital funds).
Keywords: G24; G32; G23; L20; L26; 650; accelerator; bibliometric analysis; literature review; startup; startup accelerator